2010
DOI: 10.1007/s10802-010-9432-z
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Links Between Theory of Mind, Peer Victimization, and Reactive and Proactive Aggression

Abstract: This study investigated the relation between theory of mind and reactive and proactive aggression, respectively, as well as the moderating role of peer victimization in this context. The 574 participants were drawn from a longitudinal study of twins. Theory of mind was assessed before school entry, when participants were 5 years old. Reactive and proactive aggression as well as peer victimization were assessed a year later in kindergarten. Results from multilevel regression CIHR Author Manuscript CIHR Author … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
2
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 86 publications
(158 reference statements)
3
62
2
7
Order By: Relevance
“…Development of theory of mind in children is associated with a decrease in proactive aggression. 44 Perhaps also relevant is the work of Goldberg and colleagues, 45 who found that inpatients who committed acts of aggression were differentiated from their nonaggressive peers by exhibiting significantly higher self-serving theory of mind biases, attributing more positive attributes to themselves relative to their perceptions of how others viewed them.…”
Section: Item Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of theory of mind in children is associated with a decrease in proactive aggression. 44 Perhaps also relevant is the work of Goldberg and colleagues, 45 who found that inpatients who committed acts of aggression were differentiated from their nonaggressive peers by exhibiting significantly higher self-serving theory of mind biases, attributing more positive attributes to themselves relative to their perceptions of how others viewed them.…”
Section: Item Contentmentioning
confidence: 99%
“…Many studies have found significant negative correlations between insight into illness and aggression in patients with schizophrenia. 13,44,46,47 However, medication nonadherence, positive symptoms, and psychopathy have been proposed as common-cause explanations of this covariance. Treatment noncompliance alone predicts an increase in the likelihood of violent behavior.…”
Section: Item Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ToM capacities have also been found to positively relate to traits on which psychopathic individuals score relatively low, such as agreeableness (Nettle and Liddle, 2008;Patrick et al, 2007). This latter observation, in combination with the finding that low ToM has been found to predict angry and aggressive responding in social interactions (Mohr et al, 2007;Renouf et al, 2010), could be more indicative of potential deficiencies in psychopaths' ToM.…”
mentioning
confidence: 93%
“…ToM conceptions include the capacity to understand one's own and other's mental states, to infer other's mental states and then to adapt one's behavior to others social situations [11] [12]. Some studies have identified deficits in children with EB in the recognition of emotions and the understanding of causes and consequences of emotions [13] [14] [15], difficulties in interpreting other people's behavioral intentions [16], or deficits in the understanding of beliefs [17] [18].…”
Section: Introductionmentioning
confidence: 99%